Identification of Geometrical Parameters of an Operational Railway Route Determined by the Curvature of the Track Axis - KOC, Wladyslaw (European Journal of Applied Sciences, 2022)
The paper presents a detailed procedure for determining the curvature of the track axis with the use of the moving chord method, with a view to practical application of this method to identify the geometric parameters of the operational railway track. The method of determining the coordinates of the end of the virtual chord brought forward and backward, and then determining the curvature occurring at a given measurement point, has been explained. The presented course of action is based on the use of the given calculation formulas and is of a sequential nature; there is no need to use numerical methods. As part of the curvature calculation procedure, it is also possible to determine the values of the directional angle of the route. The verification of the application possibilities of the moving chord method was carried out in the presented calculation example, on the basis of the determined Cartesian coordinates of the axis of the railway track in use. The obtained curvature plots, which clearly differ from the plots for model layouts as they have a less regular, oscillating character, which results from the track deformation and measurement error. However, this did not prevent them from making it possible to estimate the basic geometrical parameters of the measured layout. The implementation of the presented procedure should significantly improve the process of identifying the geometric layouts of the track in the horizontal plane.